Taxonomic identity of two enigmatic aquatic snake populations (Squamata: Homalopsidae: Cerberus and Homalopsis) from southern Thailand - Pauwels, Olivier S.g.; Sumontha, Montri (Zootaxa, 2016)
In their revision of the homalopsid genus Homalopsis Kuhl & Van Hasselt, Murphy et al. (2012) resurrected H. semizonata Blyth, 1855 and noted that ‘‘Frith (1977) reported on two Homalopsis from Phuket, Thailand with 40 and 42 dorsal scale rows, and 159 and 162 ventrals-scale counts within the range of H. semizonata which is found along the same coast, about 900 km to the north’’. Murphy et al. (2012), however, did not list H. semizonata from Thailand, and on their species’ distribution map they indicated an interrogation mark along the southern coast of Myanmar and the southwestern coast of peninsular Thailand. It should be noted that Murphy et al. (2012) misread Frith: while one of the two specimens reported by Frith was indeed from Phuket (‘‘from the rocky edge of a stream torrent in good forest east of Thalang, central Phuket Island’’), the other was from ‘‘Klong Nakha, 80 kilometeres [sic] south of Ranong in lowland rain forest with some clearings and dwellings’’, thus in Ranong Province, closer to the border with Myanmar. Nabhitabhata et al. (2004) recognized a single Homalopsis species in Thailand, H. buccata, which they listed for numerous provinces, including Phuket, based on Frith’s (1977) record. Among the two Homalopsis species recognized to occur in Thailand by Nabhitabhata and Chan-ard (2005), H. buccata and H. nigroventralis, none was recorded by them from Phuket Province, but H. buccata was listed from, among others, the neighbouring provinces of Phang-Nga and Ranong. Chuaynkern & Chuaynkern (2012) recognized the same two species, and listed H. buccata from, among others, the provinces of Phang-Nga, Phuket and Ranong. Cox et al. (2012) listed three Homalopsis for Thailand (H. buccata, H. mereljcoxi and H. nigroventralis), and indicated that H. mereljcoxi is the species occurring, a.o., in Phang-Nga, Phuket and Ranong provinces. Wallach et al. (2014) noted that H. semizonata lives in southern Myanmar near sea level, but also that it ‘‘possibly occurs in Phuket’’. Chan-ard et al. (2015), in their field guide whose reptile taxonomy is largely outdated (Pauwels & Grismer 2015), recognized only Homalopsis nigroventralis and H. buccata and the map for the latter indicates its presence in Phuket and Phang-Nga provinces. In the most recent synthesis on the family Homalopsidae, Murphy & Voris (2014) made however no mention of the possibility that H. semizonata occurs in Thailand. Because of the lack of voucher material, the identity of the Homalopsis living on the Indian Ocean coastal area of Thailand has thus remained poorly understood so far.